Ответы и объяснения

Лучший Ответ!
  • Katyuha85
  • почетный грамотей
2013-03-14T10:56:46+04:00

291.

2).  (4у/(2-у) - у) : (у+2)/(у-2) = - (5у-2) / (у+2)

выполним по действиям:

а). 4у/(2-у) -у = (4у²-2у+у²)/у(2-у) = (5у²-2у)/у(2-у) = (у(5у-2))/у(2-у) = (5у-2) / (2-у)

б). (5у-2) / (2-у) : (у+2)/(у-2) = (5у-2)(у-2) / (2-у)(у+2) = - (5у-2)(у-2) / (у-2)(у+2) = - (5у-2) / (у+2)

 

4). (ab/(a²-b²) - b/(b-a)) : (a-b) = (b(2a+b)/((a-b)²(a+b))

выполним по действиям:

а). ab/(a²-b²) - b/(b-a) = ab/((a-b)(a+b)) - b/(b-a) = -ab/((b-a)(a+b)) - b/(b-a) = (-ab-ab-b²)/((b-a)(a+b)) = (-2ab-b²)/((b-a)(a+b)) = (-b(2a+b)/((b-a)(a+b))

б). (-b(2a+b)/((b-a)(a+b)) : (a-b) = (-b(2a+b)/((b-a)(a+b)(a-b))  = (b(2a+b)/((a-b)(a+b)(a-b)) = (b(2a+b)/((a-b)²(a+b))

 

292.

2). (2+ a/(a+1)) * ((3a²+3a)/(12a+8)) = 0.75a

выполним по действиям:

а). 2+ a/(a+1) = (2a+2+a)/(a+1) = (3a+2)/(a+1)

б). (3a²+3a)/(12a+8) = (3a(a+1))/(4(3a+2))

в). (3a+2)/(a+1) * (3a(a+1))/(4(3a+2)) = (3a)/(4) = 0.75a

 

4). (a/(a-5) - 2a) : (11-2a)/(a-5) = a

выполним по действиям:

а). a/(a-5) - 2a = (a-2a²+10a)/(a-5) = (11a-2a²)/(a-5) = (a(11-2a))/(a-5)

б). (a(11-2a))/(a-5) : (11-2a)/(a-5) = (a(11-2a))/(a-5) * (a-5)/(11-2a) = a

 

сейчас последний пример решу....